PENGARUH LATAR BELAKANG PENDIDIKAN, PENGALAMAN, PELATIHAN DAN HUBUNGAN ANTAR KARYAWAN TERHADAP KINERJA MANTRI PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG SAMUDERA BANJARMASIN - Muhammad Teguh Nuryadin; Riswan Yunida; Shinta Febiyansari (At-Tadbir : jurnal ilmiah manajemen, 2019)
The purpose of this study was to determine the effect of educational background, experience, training and the relationship between employees on the performance of paramedics. The research method used is a quantitative method. Data collection techniques are questionnaires, observations, and interviews. The data analysis technique used is multiple linear regression data analysis techniques using SPSS for Windows software. And as many as 86 respondents. The results of this study indicate that (1) the variables of educational background, experience, training, and relations between employees have a simultaneous effect on the performance of paramedics at PT Bank Rakyat Indonesia (Persero) Tbk, Samudera Banjarmasin Branch with a F = 4,449 and a significant value of 0.003 ,(2) variable educational background does not affect the partial value(t <ttable = 1,155  <1,663),the variable does not affect the partial experiences with the value(t <ttable = -0009  <1,663),training has no effect significantly with the value (t-calc <ttable = 0.149 < 1,663), while the relationship variable between employees has a partial effect with the value (t-calc > ttable = 3.167 > 1,663), and (3) the most dominant variable is the relationship variable between employees with t-calc  = 3,167. Keywords: Background of Education, Training, Experience, Inter-employee Relations, Multiple Linear Regression